2007
DOI: 10.1021/bi700628c
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Replication of the Ring Opened Formamidopyrimidine, Fapy·dG in Escherichia coli

Abstract: Addition of hydroxyl radicals to the C8 position of 2 0-deoxyguanosine generates an 8-hydroxyguanyl radical that can be converted into either 8-oxo-7,8-dihydro-2 0-deoxyguanosine or N-(2-deoxy-D-pento-furanosyl)-N-(2,6-diamino-4-hydroxy-5-formamido-pyrimidine) (Fapy-dG). The Fapy-dG adduct can adopt different conformations and in particular, can exist in an unnatural a anomeric configuration in addition to canonical b configuration. Previous studies reported that in 5 0-TGN-3 0 sequences, Fapy-dG predominantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 53 publications
6
70
0
Order By: Relevance
“…Comparison of the mutagenesis caused by 8-oxoG and FapyG was performed in simian kidney cells (COS-7), and more Gua → Thy transversion mutations were caused by FapyG than by 8-oxoG in several sequence contexts (31). However, a recent study showed that in E. coli, the mutagenicity of 8-oxoG is greater than that of FapyG (32). It is also possible that the reduced mutagenicity we observed in the triple mutant strain is partially due to the further oxidation product of 8-oxoG, Sp, which gives rise to a combination of Gua → Thy and Gua → Cyt transversion mutations (33,34) and can be recognized by MmuNeil3.…”
Section: Mmuneil3mentioning
confidence: 99%
“…Comparison of the mutagenesis caused by 8-oxoG and FapyG was performed in simian kidney cells (COS-7), and more Gua → Thy transversion mutations were caused by FapyG than by 8-oxoG in several sequence contexts (31). However, a recent study showed that in E. coli, the mutagenicity of 8-oxoG is greater than that of FapyG (32). It is also possible that the reduced mutagenicity we observed in the triple mutant strain is partially due to the further oxidation product of 8-oxoG, Sp, which gives rise to a combination of Gua → Thy and Gua → Cyt transversion mutations (33,34) and can be recognized by MmuNeil3.…”
Section: Mmuneil3mentioning
confidence: 99%
“…46,[94][95][96][97] In contrast FapyG, like 8-oxoguanine, can be bypassed by Klenow exo À DNA polymerase which inserts adenine opposite 98 and in E. coli leads to G-T transversions. In a single sequence context, FapyG is not as mutagenic in E. coli as it is in simian kidney cells; 99,100 however, recent studies suggest that FapyG is as potent a premutagenic lesion in E. coli as 8-oxoguanine. 101 Similar to guanine, the 8-position on the imidazole ring of adenine is also susceptible to oxidation resulting in 8-oxoadenine.…”
Section: Consequences Of Unrepaired Oxidative Dna Damagesmentioning
confidence: 99%
“…Taken together these data supported the idea that 8-oxoguanine is a biologically important, potentially mutagenic oxidative DNA lesion. However recent studies have shown that unmethylated FapyG is also a good substrate for Fpg (18,19) and like 8-oxoG, A can also be incorporated opposite FapyG (20,21) and the incorporated A can be removed by MutY (22). FapyG, which is formed from the same adduct radical as 8-oxoG (23), appears to be responsible for a substantial number of mutations originally attributed to 8-oxoG and thus is also a biologically relevant substrate (24).…”
Section: Introductionmentioning
confidence: 99%